Knowledge, attitude, and factors affecting implementation of birth companionship during labor among obstetricians, nurses and pregnant women at a tertiary care teaching hospital - Pooja Lathwal; Himanshu Vyas; Pratibha Singh; T Deviga (Journal of Public Health and Primary Care, 2022)
Context: Birth companions are women who have experienced the process of labor and provide continuous one-to-one support to the other women who are experiencing the process of labor and childbirth. Aim: This study aimed to assess knowledge, attitude, and factors affecting the implementation of birth companionship among obstetricians, nurses, and pregnant women. Settings and Design: Nonexperimental quantitative research approach with a descriptive design carried out at All India Institute of Medical Sciences, Jodhpur, Rajasthan. Materials and Methods: Data were collected from 25 obstetricians, 15 nurses selected by consecutive sampling technique, and 120 pregnant women selected by purposive sampling technique. Data collection tool included a structured knowledge questionnaire, an attitude Likert scale, and a checklist to assess factors affecting the implementation of birth companionship. Statistical Analysis Used: Data were entered into a master sheet and SPSS 16 version was used for the descriptive and inferential statistical analysis. Results: Most of the obstetricians (60%) and pregnant women (59.2%) had fair knowledge, whereas nurses (53%) had good knowledge regarding birth companionship. Most of the obstetricians (96%), nurses (73%), and pregnant women (81.7%) had positive attitudes regarding birth companionship. Breach of privacy of other mothers, less availability of space to accommodate birth companion, and nonavailability of ideal birth companion were the most common factors reported to affect the implementation of birth companionship by the obstetricians and nurses , whereas long distance of hospital from home and apprehension due to a known person's presence were the factors reported by pregnant women. Knowledge level and attitude level of the pregnant women had a significant association with age (P = 0.000) and parity (P = 0.042), respectively.